Acupuncture and stroke motor rehabilitation: a decade of evidence synthesis via systematic mapping (2015–2024) - Ke, Chao; Zhou, Zhuo; Sun, Mengzi; Shi, Wenying; Xu, Min; Su, Rusin; Zhou, Yilin; Ouyang, Zhiwen; Yin, Jiaxin; Zhang, Wei (Frontiers in Neurology, 2025)
BackgroundAcupuncture has shown efficacy in the treatment of post-stroke motor impairment, for which it has newfound renown on the world stage. However, the knowledge base has not yet been reviewed in terms of international clinical trial design. This study systematically reviews the distribution and status of clinical research on acupuncture for treating post-stroke motor dysfunction within the last 10 years.MethodsWe conducted a comprehensive search of four Chinese and three English databases from 1 January 2015 to 8 August 2024. We included randomised control trials (RCTs) with a control group. The study participants were diagnosed with post-stroke motor dysfunction according to clear diagnostic criteria regardless of nationality, race, sex, age, disease duration, or condition. The interventions included acupuncture administered alone or in combination with other acupuncture or non-acupuncture interventions. We included studies comparing different acupuncture therapies; acupuncture with sham treatments; acupuncture with other therapies; and compound effects. No restrictions were set on the type of outcome. Data were synthesised and visually analysed using Excel (2003), Office (2009), CiteSpace, SPSS Modeller 18.0, Hiplot, BioRender, and ChiPlot. Scientometric and visualisation analyses of the keywords were performed using CiteSpace. The Apriori algorithm in SPSS Modeller 18.0 was used to conduct an association analysis between acupoints and acupuncture therapies. Risk of bias assessments were performed using Cochrane RoB 2.0.ResultsA total of 3,645 RCTs were included in the final review. Most studies were concentrated in China. Significant heterogeneity was observed in participants characteristics, intervention protocols, control groups, and clinical design. The RCTs showed a potentially high risk of bias owing to a lack of concealment methods and/or blinding.ConclusionThis study highlights evidence supporting the applicability of acupuncture as an effective and safe treatment for post-stroke motor dysfunction. The findings provide a useful reference for informing the design of future experimental and clinical studies, as well as guidance for clinical diagnosis and management.